∫ − 1 1 ∂ x ∂ ( 1 + e x 1 1 ) d x
If the above integral can be expressed as C + D e E A + B e , where A , B , C , D and E are integers, with least values, also A > 0 and e is the Napier's constant . Find A + B + C + D + E
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hi, can you please tell me what is the logical mistake if I just directly take the limits without considering whether y' is even or odd function. Thanks
Log in to reply
Sorry, I can't explain it.
I noted that while y ′ ( x ) is even, but y ( x ) and I assumes the integral for 0 < x ≤ 1 was correct. My answer may not be correct.
Problem Loading...
Note Loading...
Set Loading...
Consider the following:
y y ′ ( x ) y ′ ( − x ) = 1 + e x 1 1 = ∂ x ∂ ( 1 + e x 1 1 ) = x 2 ( 1 + e x 1 ) 2 e x 1 = x 2 ( 1 + e − x 1 ) 2 e − x 1 = e x 2 ⋅ x 2 ( 1 + e − x 1 ) 2 e x 2 ⋅ e − x 1 = x 2 ( e x 1 + 1 ) 2 e x 1 = y ′ ( x )
Therefore, y ′ ( x ) is an even function. Now consider:
I = ∫ − 1 1 ∂ x ∂ ( 1 + e x 1 1 ) d x = ∫ − 1 1 y ′ ( x ) d x = 2 ∫ 0 1 y ′ ( x ) d x = 2 ∫ 0 1 ∂ x ∂ y ⋅ d x = 2 ∫ y ( 0 ) y ( 1 ) d y = 2 ⋅ 1 + e x 1 1 ∣ ∣ ∣ ∣ 0 1 = 1 + e 2 Since y ′ ( x ) is even.
⟹ A + B + C + D = 2 + 1 + 1 + 1 = 5